PENGARUH PELATIHAN, KOMUNIKASI DAN SINERGI KERJA TERHADAP JENJANG KARIR PADA KARYAWAN PT BUDI GUNA LAUT ABADI - Wanto Satio (Skena Bisnis, 2024)
The purpose of this study was to deteminate the effect of training, communication and work synergy on employee career paths at PT Budi Guna Laut Abadi. The type of research used in this study is a quantitative descriptive type carried out by collecting data using questionnaires and analyzing statistical testing data. Based on this study because the total population is not greater than 100 employee, the author takes 100% of the total population at PT Budi Guna Laut Abadi, which is as many as 65 employee. The Instruments used are validity and reliability test. The results of this study showed that simultaneously, training, communication and work synergy had a significant effect on the career path with a Fcount value > Ftabel;20,458 > 2.75. Partially, training has a significant positive effect on the career path with tcount value > ttabel;3,985 > 1,999. Partially, communication has a significant positive effect on the career path with a tcount value > ttabel; 4,268 > 1,999. and partially, work synergy has a significant positive effect on the career path with a tcount value > ttabel or 5,026 > 1,999.